Preparedness of health facilities to deal with factors contributing to HIV drug resistance in adult patients on anti - retroviral therapy : a case study of a clinic in Tsholotsho District - Dube, Chiratidzo (Midlands State University, 2020)
HIV infection was first discovered in 1980s in Zimbabwe. The government had designed many strategies to deal will HIV infection. These strategies included use of standardised guidelines and policies such as HIV policy and HIV treatment guidelines. These measures were designed to prevent HIV drug resistant infection by promoting viral load suppression. The level of preparedness to deal with factors contributing to development of drug resistant HIV infection amongst adult people living with HIV was established. This chapter provided background information to the problem, statement of the problem, research questions and objectives, significance of the study, delimitations and limitations of the study. A summary of the chapter was provided.